Generation of Q-switching and mode-locking pulses with yttrium oxide based saturable absorber / Noorsyamila Fazyanti Mustafa - Noorsyamila Fazyanti , Mustafa (2019)
The report aims to a new saturable absorber (SA) material based on metal oxide for both Q-switching and mode-locking pulses generations. Yttrium Oxide (Y2O3) was successfully proposed and demonstrated for realizing both Q-switched and mode-locked Erbium-doped Fiber Lasers (EDFLs). The film SA was prepared through solution casting technique by embedding the Y2O3 powder into a polyvinyl alcohol (PVA) host film. With the SA, the Q-switched laser was demonstrated with the frequency is tunable from 70.22 kHz to 99.2 as the pump power is varied from 52.4 mW to 181.5 mW. The shortest pulse width of 2.97 μs and the maximum pulses energy of 180 nJ were obtained at the pump power of 181.5 mW. By incorporating the film SA along with 200 m long single mode fibre (SMF) into another EDFL cavity, the mode-locked laser was also realized to operate at 1 MHz repetition rate with 460 ns pulse width at pumping power within 181.5 – 246.0 mW. The highest pulse energy was obtained at 25.2 nJ. These indicators suggest that Y₂O₃ film is a good passive SA that can be used to generate both Q-switched and mode-locked pulsed laser operating at 1.55 μm region.